Academic Writing: Types, Elements, and Strategies - Abdulaziz Ahmed Mohammed Ahmed (IJLHE: International Journal of Language, Humanities, and Education, 2022)
Academic writing is difficult. It requires a complex combination of generating ideas, selecting the idea that are appropriate to the writing tasks, translating these into a text and a polishing the text to produce a reasonable and presentable documents. In doing this, a writer has to bring out not only his or her own thoughts but also to make more and enough connection with the community whom writing is being written. This paper will highlight the different kinds of academic writings and the important strategies a researcher should follow to build up a good comprehensible and logical scientific writings and research papers, and it will help to explore the relationships between writing strategies and success as well. The writing process for most writers and expertise tend to be recursive rather than simple linear progression starting with planning and finishing with revising. The paper will elucidate and well shown different kinds of strategies and the way of structuring a good scientific and academic piece of writing. The article will also explore and explain the value of academic writing in the field of research studies. It presents the guidelines that can help to analyses the academic writing process, but also that no amount of theorizing and intellectualizing of writing is going on to make more successful writing patterns unless accompanied by an undertaking to engage in practical strategies and to plan effective writing tactics. The academic value of the writing can then be evaluated and if they wish, ones maker can go back to notice the original sources to find out whether ones have been honest and accurate in the use of data ,ideas and information.